On Markovian Short Rates in Term Structure Models Driven by Jump-Diffusion Processes - Pavel V. Gapeev; Uwe Küchler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
We study a bond market model and related term structure of interest rates where prices of zero coupon bonds are driven by a jump-diffusion process. We present a criterion on the deterministic forward rate volatilities under which the short rate process is Markovian and give sufficient conditions on the bond price volatility structure depending on the short rate for existing a finite-dimensional Markovian realization of the term structure model.
urn:nbn:de:kobv:11-10050780
Keywords: 330; Börsenkurs; Rentenmarkt; Zinsstruktur; Markovscher Prozess; Theorie